Racial Disparities in Kidney Transplant Waitlist Appearance in Chicago: Is it Race or Place? - Peng, Robert B. (Clin Transplant, 2018)
BACKGROUND. Prior work has demonstrated how neighborhood poverty and racial composition impact racial disparities in access to the deceased donor kidney transplant waitlist, both nationally and regionally. We examined the association between neighborhood characteristics and racial disparities in time to transplant waitlist in Chicago, a diverse city with continued neighborhood segregation. METHODS. Using data from the United States Renal Data System (USRDS) and the US Census, we investigated time from dialysis initiation to kidney transplant waitlisting for African American and white patients in Chicago using cause-specific proportional hazards analyses, adjusting for individual socio-demographic and clinical characteristics, as well as neighborhood poverty and racial composition. RESULTS. In Chicago, African Americans are significantly less likely than whites to appear on the renal transplant waitlist (HR 0.73, p<0.05). Compared to whites in non-poor neighborhoods, African Americans in poor neighborhoods are significantly less likely to appear on the transplant waitlist (HR 0.61, p<0.05). Over 69% of African Americans with ESRD live in these neighborhoods. CONCLUSIONS. Consistent with national data, African Americans in Chicago have a lower likelihood of waitlisting than whites. This disparity is explained in part by neighborhood poverty, which impacts the majority of African American ESRD patients in Chicago.